Venous ulcers of the lower limb: Where do we stand? - Chatterjee Sasanka S. (Indian Journal of Plastic Surgery)
Venous ulcers are the most common ulcers of the lower limb. It has a high morbidity and results in economic strain both at a personal and at a state level. Chronic venous hypertension either due to primary or secondary venous disease with perforator paucity, destruction or incompetence resulting in reflux is the underlying pathology, but inflammatory reactions mediated through leucocytes, platelet adhesion, formation of pericapillary fibrin cuff, growth factors and macromolecules trapped in tissue result in tissue hypoxia, cell death and ulceration. Duplex scan with colour flow is the most useful investigation for venous disease supplying information about patency, reflux, effects of proximal and distal compression, Valsalva maneuver and effects of muscle contraction. Most venous disease can be managed conservatively by leg elevation and compression bandaging. Drugs of proven benefit in venous disease are pentoxifylline and aspirin, but they work best in conjunction with compression therapy. Once ulceration is chronic or the patient does not respond to or cannot maintain conservative regime, surgical intervention treating the underlying venous hypertension and cover for the ulcer is necessary. The different modalities like sclerotherapy, ligation and stripping of superficial varicose veins, endoscopic subfascial perforator ligation, endovenous laser or radiofrequency ablation have similar long-term results, although short-term recovery is best with radiofrequency and foam sclerotherapy. For deep venous reflux, surgical modalities include repair of incompetent venous valves or transplant or transposition of a competent vein segment with normal valves to replace a post-thrombotic destroyed portion of the deep vein.